191 The Effect of Covid-19 on the Management of Acute Ureteric Colic in a Tertiary Hospital. (19th August 2022) - Sen, P; Edison, E; Smith, D
Abstract: Introduction: The Covid-19 pandemic forced changes to care pathways. We have analysed the difference in provision of care to patients presenting with ureteric colic during the pandemic (PC) compared to a pre-pandemic cohort (PPC). Method: A list was generated of all CT KUB scans requested in the emergency department. Imaging and notes were reviewed to identify acute ureteric colic presentations in September to December 2019 and 2020. Statistical significance was calculated using either the Student T-test or Chi-squared test. Results: There were 92 patients in the PC, and 107 in the PPC. Primary treatment was provided for more patients during the pandemic (25% vs 10%, p<0.05), mainly by extracorporeal shockwave therapy (ESWL, 21% vs 7%, p<0.05). The rate of conservative management (64% vs 76%, p>0.05), temporising stent (11% vs 14%, p>0.05), and nephrostomy insertion (1% vs 1%, p>0.05) was similar in PC and PPC. The PC had a shorter time to intervention (17 vs 39 days, p<0.05), to ESWL (4 vs 12 days, p>0.05), to ureteroscopy (35 vs 45 days, p>0.05), and to stone passage confirmation (44 vs 91 days, p<0.05) respectively. There was no follow up for 15% and 30% respectively (p<0.05). Conclusion: During the pandemic, a reduction in electives created capacity for urgent interventions, (21% vs 7% ESWL, 4 vs 12 waiting days). Accordingly, the stone passage confirmation time was more than halved (44 vs 91 days). In accordance with recommendations from NICE, TISU and GIRFT, this demonstrates the importance of ringfencing ESWL, particularly as we emerge from the pandemic.